The Leopold Formation: An Upper Silurian Intertidal/Supratidal Carbonate Succession on Northeastern Somerset Island, Arctic Canada - Jones, Brian; Dixon, Owen A. (Canadian Journal of Earth Sciences, 1975)
The name Leopold Formation is proposed for a thick and distinctive Upper Silurian stratigraphic succession, approximately 1000 ft (305 m) thick, on northeastern Somerset Island. This new formation consists largely of dolomitic rocks which formed in tidal flat environments analogous to those around the modern Persian Gulf. Dolostone, dolomitic limestone, sandy limestone, sandy dolostone and rocks containing mixtures of micritic calcite, dolomite and detrital material are predominant, and are associated with minor amounts of sandstone, evaporites and micritic, shelly, intraclastic and oncolitic limestone. Most of the dolomite is secondary and complex facies patterns in the formation reflect initial complexity in sediment distribution that was accentuated by irregular but extensive diagenetic dolomitization of the tidal flat sediments.The distribution of the intertidal/supratidal rocks and the nature of the immature detrital materials they contain are strong evidence of an important, but previously unrecognized, contemporaneous land mass north and northeast of Somerset Island.The formation contains a markedly restricted in situ fauna of eurypterids, ostracods, gastropods, ostracoderms and rare brachiopods. Stromatolites are common and some stromatolitic units are sufficiently distinctive and laterally persistent to be used for local correlation.Conodonts and other faunal elements indicate that the Leopold Formation is of Pridolian age (Upper Silurian). It correlates with the upper part of the Read Bay Formation to the west and northwest, a succession which, in contrast, consists predominantly of subtidal marine limestones.